Objective or Perception-Based: A Debate on the Ideal Measure of Corruption - Pelizzo, Riccardo; Janenova, Saltanat; Baris, Omer (Cornell International Law Journal, 2017)
In Kazakhstan, several institutions have developed new measures of corruption. This Article addresses the doubts that empirical analyses have raised as to whether and to what extent existing measures of corruption provide valid and reliable estimates of corruption levels in Kazakhstan. Domestic institutions decided to develop the new measures after exploring reasons international measures seemed to be failing to provide a proper assessment of corruption in the country, with the hope that they could generate better estimates of corruption levels across different regions, sectors, and time...
Keywords: measure of corruption; corruption